(untitled) (Olhares, 2025)
I dance in nature with my body, as if flowers I were. I feel the perfume, the sun that warms them, the rain that refreshes them, the cold that ennobles them, the wind that gives them movement. I am not always a beautiful flower: sometimes I am crooked, but I am reborn from my mud to my skin, I rise above the earth where I step, and I am alive in the now. Sometimes, my “earth-feet” speak for themselves and step as in a dance of growth and learning. I keep evolving in the midst of many searches through my crooked body and make the defect a unique beauty.